FINANCIAL RESOURCES SEBAGAI FAKTOR PENENTU DALAM IMPLEMENTASI KEBIJAKAN PENDIDIKAN - Lantip Diat Prasojo (Prodi Manajemen Pendidikan Jurusan Administrasi Pendidikan Fakultas Ilmu Pendidikan UNY, 2010)
Abstract The issue of financial resources as strategic factor in the implementation of educational policies usually led to the provision of funds or education budgets which are generally required in the large nominal amount. In the context of the scientific implementation and financial resources not only leads to provision of funds or the budget, but includes other factors, such as Human Resources (HR), facilities, and others. Financial resources which are consist of resources, human resources and stakeholders are the three factors that very important and directly related to the implementation of education policy. Implementation of education policy is one of public policy so that stakeholders should become a part of the study in its policy analysis. Key words: financial resources